2019
DOI: 10.1038/s41582-018-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation: current challenges and future directions

Abstract: The clinical use of deep brain stimulation (DBS) is among the most important advances in the clinical neurosciences in the past two decades. As a surgical tool, DBS can directly measure pathological brain activity and can deliver adjustable stimulation for therapeutic effect in neurological and psychiatric disorders correlated with dysfunctional circuitry. The development of DBS has opened new opportunities to access and interrogate malfunctioning brain circuits and to test the therapeutic potential of regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
644
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 900 publications
(727 citation statements)
references
References 143 publications
3
644
0
7
Order By: Relevance
“…There is widespread and growing interest in using brain stimulation for various research, clinical, and practical purposes [Borchers et al, 2012, Ezzyat and Rizzuto, 2018]. In many cases, the stimulation parameters that are chosen for a given task are modeled after the ones used in other protocols or in other subjects [Lozano et al, 2019]. Our work supports a tailored approach to choosing stimulation parameters, by customizing the parameters for each person based on how different types of stimulation affects their own ongoing brain signals as well as the electrophysiological pattern of interest.…”
Section: Discussionmentioning
confidence: 99%
“…There is widespread and growing interest in using brain stimulation for various research, clinical, and practical purposes [Borchers et al, 2012, Ezzyat and Rizzuto, 2018]. In many cases, the stimulation parameters that are chosen for a given task are modeled after the ones used in other protocols or in other subjects [Lozano et al, 2019]. Our work supports a tailored approach to choosing stimulation parameters, by customizing the parameters for each person based on how different types of stimulation affects their own ongoing brain signals as well as the electrophysiological pattern of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chronic deep brain stimulation in this area improves chronic dysphoric conditions (Mayberg et al, 2005). However, with evidence accumulating that the most effective electrodes in deep brain stimulation are situated in or nearby white matter fiber tracts, rather than in grey matter proper, recent deep brain stimulation approaches are explicitly targeting white matter fiber structures (Baldermann et al, 2019;Lozano et al, 2019). Considering the effective electrical stimulation of area 25 (Johansen-Berg et al, 2008), this region is innervated and visited by the nearby AmF, suggesting the hypothesis that the physiological effects may be primarily ascribed to the AmF pathway and the regions it interconnects.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study examining deep brain stimulation (DBS) at 10 kHz frequencies (10 kHz‐DBS; also called ultra‐high frequency DBS), we reported that acute 10 kHz‐DBS appears safe and may be effective in improving motor symptoms in patients with movement disorders . Furthermore, 10 kHz‐DBS stimulation may have the potential to reduce stimulation‐induced adverse effects, such as transient paresthesia and impaired speech, which are often encountered with DBS at conventional frequencies . Selecting the optimal stimulation frequency for DBS can be challenging.…”
Section: Introductionmentioning
confidence: 99%